Learning cities for adult learners - Scott, Leodis (New directions for adult and continuing education ;, 2015)
Learning cities call for a connection of adult education to elementary, secondary, and postsecondary institutions along with vocational and corporate workspaces. This volume considers how "learning cities for adult learners" could be created in America that promote lifelong learning and education. Encouraging a widespread approach to educate and learn across disciplines, within communities, and inside the minds of all people, topics covered include: workplace and organizational learning, community engagement and service learning, public libraries and cooperative extension, and l.